CURRENT STATUS AND PROSPECTS OF PROFESSIONAL COOPERATION IN HIGHER EDUCATION BETWEEN CHINA AND KAZAKHSTAN (Journal of Oriental Studies, 2026)
Sino-Kazakh higher education cooperation has undergone more than three decades of development, with its focus progressively shifting away from singular language education toward more diversified and in-depth professional cooperation. However, current academic research predominantly remains at the level of language education, lacking systematic analysis of the development status, operational models, and underlying challenges of professional cooperation, as well as in-depth examination of the inherent transformation trajectory and internal logic. Consequently, these studies fail to adequately address the practical demands of deepening bilateral professional cooperation in higher education.This study systematically reviews the evolutionary trajectory, primary models, and underlying constraining factors of Sino-Kazakh professional cooperation in higher education. Employing textual analysis, case study analysis, and comparative analysis, the research comprehensively collects and examines relevant policy documents, cooperative development data, existing academic literature, and publicly available information from the official websites of universities in both countries.The findings reveal that Sino-Kazakh higher education cooperation has evolved through three distinct phases: from scattered language education exchanges and cooperation, to deepening collaboration underpinned by regional education platforms, and subsequently to the transformation of cooperation models through the joint participation of government, industry, and educational institutions. The cooperation has now entered a deepening phase characterized by discipline-led professional engagement. The two sides have established a diversified and synergistic professional cooperation system encompassing seven primary models: Confucius Institutes, exchange student programmes, summer camps, dual-degree programmes, joint educational institutions, Luban Workshops, and joint laboratories. Nevertheless, institutional barriers—including insufficient alignment of professional curriculum systems, lack of standardized credit recognition and transfer mechanisms, and absence of mutual recognition for quality assurance standards—continue to constrain the depth of collaboration.This study constructs a systematic analytical framework for Sino-Kazakh professional cooperation, expands the research perspective on the transition from language to professional cooperation in bilateral higher education, and clarifies the internal logic underlying each phase of transformation. The research provides practical reference for universities in both countries to optimize cooperation mechanisms, offers decision-making support for resolving common institutional challenges, and lays the groundwork for subsequent digital education cooperation and joint curriculum development.Keywords: Higher education, Professional cooperation, Collaborative models, Kazakhstan, China.